Numerical Simulation of Nanoparticle Fraction for the Peristaltic Flow of a Six Constant Jeffrey’s Fluid Model - Sher Akbar, Noreen; Nadeem, S.; Lee, Changhoon; Hayat Khan, Zafar (Current Nanoscience, 2013)
In the present article, peristaltic nanofluid flow of an incompressible six constant Jeffrey’s fluid model in an asymmetric channel has been discussed. The flow has been analyzed in a wave frame of reference moving with the wave speed c. The problem formulation has been done for two dimensional and two directional flow under long wave length and low Reynold’s number approximation. The numerical solutions for the velocity, temperature and nanoparticle fraction and pressure rise are calculated using fourth and fifth order Runge-Kutta-Fehlberg method. The graphical results are presented to interpret the behaviour of various flow parameters.
Keywords: Six constant Jeffrey’s model